Extending the national childcare scheme to childminders: Cost and distributional effect - Karina Doorley; Dora Tuda; Luke Duggan (The Economic and Social Research Institute (ESRI), 2023)
A series of studies have found that, prior to the introduction of the National Childcare Scheme (NCS), parents in Ireland faced some of the highest childcare costs among OECD countries. To improve childcare affordability, in 2019 the Government introduced the NCS, which awards universal and means-tested childcare subsidies to families using registered childcare. In this report we estimate the potential cost and distributional impact of extending the NCS to a form of mostly unregistered childcare: childminders who care for children in the childminder's home. We estimate that this reform would increase the cost of the NCS to the Exchequer by exteuro35-121 million per annum (8 per cent to 29 per cent of the current cost), depending on take-up of the subsidy. Such a reform would decrease the cost of childminder-based care by exteuro100 per month, per child, and would mainly benefit middle-income households. This could also have wider impacts, on both the demand for centre-based childcare and mothers' labour supply.
Keywords: 330